2014
DOI: 10.1111/sms.12250
|View full text |Cite
|
Sign up to set email alerts
|

Provocative mechanical tests of the peripheral nervous system affect the joint torque‐angle during passive knee motion

Abstract: This study aimed to determine the influence of the head, upper trunk, and foot position on the passive knee extension (PKE) torque-angle response. PKE tests were performed in 10 healthy subjects using an isokinetic dynamometer at 2°/s. Subjects lay in the supine position with their hips flexed to 90°. The knee angle, passive torque, surface electromyography (EMG) of the semitendinosus and quadriceps vastus medialis, and stretch discomfort were recorded in six body positions during PKE. The different maximal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…a significant increase in EMG activity. Therefore, torque (resistive force to elongation during the stretching maneuver) may be considered passive because the biological tissue deformation happened with minimal participation of voluntary or reflex muscle contractions 20 . Stiffness is the resistive force estimation of MTU in response to changes in its length 9 , whereas energy is the biological tissues’ ability to absorb work that can either be reused in subsequent movements or dissipated as heat 21 .…”
Section: Discussionmentioning
confidence: 99%
“…a significant increase in EMG activity. Therefore, torque (resistive force to elongation during the stretching maneuver) may be considered passive because the biological tissue deformation happened with minimal participation of voluntary or reflex muscle contractions 20 . Stiffness is the resistive force estimation of MTU in response to changes in its length 9 , whereas energy is the biological tissues’ ability to absorb work that can either be reused in subsequent movements or dissipated as heat 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Cruz-Montecinos et al [10] reported "a significant correlation between the pelvic anteversion (forward tilting), in a long sitting position (knees fully extended), and the displacement of the deep fasciae of the gastrocnemius medialis, supporting the concept of myofascial tissue connectivity. Thus, fasciae could sustain notable stress levels during stretching maneuvers that involve polyarticular motion such as the slump position or straight-leg raising" [11]. Together, these findings strongly suggest that maximal ROM may be limited by non-muscular structures such as fascia tissue.…”
Section: Introductionmentioning
confidence: 95%
“…Nerves have traditionally been suggested in reducing ROM observed in some clinical tests. For instance, knee ROM in extension is significantly reduced when the patient is placed in the slump position (i.e., maximal lumbar and cervical flexion) compared to a neutral head position [18][19][20]. The change in nerve tension is often proposed to explain the distant decrease in ROM at the knee joint [18], particularly in clinical scenarios in which the nerve in question may already be irritated and there is amplification of the discomfort in response to a limited change in strain.…”
Section: The Important Role Of Non-muscular Structuresmentioning
confidence: 99%